FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WAJIB PAJAK MENGGUNAKAN JASA KONSULTAN PAJAK - Grace Martha Thereisya Oba; Regina Beatrix Takakobi; Toar Romario Sigar (Tangkoko: Jurnal Manajemen dan Akuntansi, 2026)
Taxes are a source of state revenue to support development financing and public services. However, taxpayer compliance in Ternate City still presents problems. This study aims to analyze the influence of tax knowledge, taxpayer motivation, and tax sanctions on taxpayer interest in using tax consultant services, both partially and simultaneously. This study uses a quantitative approach. Primary data were obtained through questionnaires. The research instrument was measured using a Likert scale. The research data were analyzed using SPSS 31.0. The results of the study indicate that tax knowledge and tax sanctions partially do not significantly influence taxpayer interest in using tax consultant services. Meanwhile, taxpayer motivation partially has a significant effect on taxpayer interest in using tax consultant services. The results of the simultaneous test show that tax knowledge, taxpayer motivation, and tax sanctions jointly influence taxpayer interest in using tax consultant services. These findings indicate that taxpayer decisions to utilize professional services are not only determined by an understanding of tax regulations and the risk of sanctions, but are also influenced by internal.